Signature of cascade transitions between interlayer excitons in a moiré superlattice - Tan, Qinghai (2023)
A moiré superlattice in transition metal dichalcogenides heterostructure provides an exciting platform for studying strongly correlated electronics and excitonic physics, such as multiple interlayer exciton (IX) energy bands. However, the correlations between these IXs remain elusive. Here, we demonstrate the cascade transitions between IXs in a moiré superlattice by performing energy- and time-resolved photoluminescence measurements in the MoS_{2}/WSe_{2} heterostructure. Furthermore, we show that the lower-energy IX can be excited to higher-energy ones, facilitating IX population inversion. Our finding of cascade transitions between IXs contributes to the fundamental understanding of the IX dynamics in moiré superlattices and may have important applications, such as in exciton condensate, quantum information protocols, and quantum cascade lasers.